Community Relationship Quality and Reincarceration Following Rural Drug-Using Women’s Reentry From Jail - Tillson, Martha (Criminal justice and behavior, 2022)
Interpersonal relationships and social support are important factors in women’s successful reentry from incarceration, but limited research has explored the role of women’s relationships to their communities during the reentry process. In the current study, women were recruited from three rural Appalachian jails, screened for high-risk behaviors (including drug use and unprotected sex), and interviewed at 12 months postrelease (N = 339). Interviews included the Relational Health Indices–Community scale, a validated measure of women’s relationships in community contexts, with subscales for empowerment/zest, engagement, and authenticity. Women who were reincarcerated during the 12-month postrelease period (43.4%) were younger, less employed, more likely to have used illicit drugs, and reported lower-quality community relationships at 12-month follow-up. Multivariate logistic regression models indicated that the effect of community relationships may be driven by the engagement and empowerment/zest constructs. Results suggest that community connectedness may relate to more successful reentry outcomes for rural women.